2020
DOI: 10.3847/1538-4357/ab6aa0
|View full text |Cite
|
Sign up to set email alerts
|

On the Wind-driven Relaxation Cycle in Accretion Disks

Abstract: A disk wind can cause perturbations that propagate throughout the disk via diffusive processes. On reaching the inner disk, these perturbations can change the disk luminosity, which in turn, can change the wind mass loss rate,Ṁ w . It has been argued that this so-called "wind driven relaxation cycle" might explain the observed variability in some disk accreting objects. Here, we study the response of the innermost mass accretion rateṀ a to the loss of matter at different rates and radii. We allow the wind laun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The oscillation periods predicted by Shields et al (1986) are comparable to those observed in GRS 1915+105, but the source appears to be an order of magnitude below the critical Ṁwind / Ṁacc threshold. A recent numerical study by Ganguly & Proga (2020) has found that oscillations manifest at lower ratios, perhaps even at Ṁwind / Ṁacc ≃ 6. Our estimate of the loss rate would approach this threshold if the wind was launched vertically.…”
Section: Discussionmentioning
confidence: 99%
“…The oscillation periods predicted by Shields et al (1986) are comparable to those observed in GRS 1915+105, but the source appears to be an order of magnitude below the critical Ṁwind / Ṁacc threshold. A recent numerical study by Ganguly & Proga (2020) has found that oscillations manifest at lower ratios, perhaps even at Ṁwind / Ṁacc ≃ 6. Our estimate of the loss rate would approach this threshold if the wind was launched vertically.…”
Section: Discussionmentioning
confidence: 99%
“…Accretion disk winds can also be launched from the outer disk via thermal driving, and this process could be important in creating the central X-ray corona and regulating the overall mass accretion rate through the disk (Shakura & Sunyaev 1973;Begelman et al 1983;Shields et al 1986). However, new numerical simulations suggest that the regulating effects of a wind are likely to be more modest (Ganguly & Proga 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is an interesting possibility, however, the light curves generated by such an instability do not, and cannot resemble, even remotely what is observed in HLX-1 (see e.g. Shields et al 1986;Ganguly & Proga 2020).…”
Section: Hlx-1 In Eso 243-49mentioning
confidence: 92%